Evaluation and development of methods for sustainable agriculture and environmental conservation in China (JIRCAS, 2010)
Contents: Cycles of major elements in agro-ecosystems in Huan-Huai-Hai plain and their controls, evaluation of nitrogen losses in agro-ecosystems in Jing-Jin-Tang region, evaluation of the environmental impact of non-point sources in Taihu catchments,...